Đáp án+Giải thích các bước giải:
`1)2(x-3)+5=3`
`⇔2(x-3)=-2`
`⇔x-3=-1`
`⇔x=2`
pt có nghiệm:`x=2`
`2)3x(x-2)+2x(2-x)=x^2-8`
`⇔3x^2-6x+4x-2x^2=x^2-8`
`⇔x^2-2x=x^2-8`
`⇔-2x=-8`
`⇔x=4`
pt có nghiệm:`x=4`
`3)3(5x-1)-x(x+1)+x^2=14`
`⇔15x-3-x^2-x+x^2=14`
`⇔14x-3=14`
`⇔14x=17`
`⇔x=17/14`
pt có nghiệm:`x=17/14`
`4)4x(x+2)+x(4-x)=3x^2+12`
`⇔4x^2+8x+4x-x^2=3x^2+12`
`⇔3x^2+12x=3x^2+12`
`⇔12x=12`
`⇔x=1`
pt có nghiệm:`x=1`
`5)x^2-x(x+2)=6`
`⇔x^2-x^2-2x=6`
`⇔-2x=6`
`⇔x=-3`
pt có nghiệm:`x=-3`
`6)5(x-2)+2(x+3)=10`
`⇔5x-10+2x+6=10`
`⇔7x-4=10`
`⇔7x=14`
`⇔x=2`
pt có nghiệm:`x=2`
`7)3x(x+5)-2(x+5)=3x^2`
`⇔3x^2+15x-2x-10=3x^2`
`⇔3x^2+13x-10=3x^2`
`⇔13x-10=0`
`⇔13x=10`
`⇔x=10/13`
pt có nghiệm:`x=10/13`